Formalin and 2.5% Glutaraldehyde/2% Paraformaldehyde in 0.1 M Cacodylate Buffer Inactivation Protocols to Ensure the Proper Fixation of Positive Sense RNA Viruses and Genomic Material Prior to Removal from Containment - Lauren E. Panny; Ashley E. Piper; Christina L. Gardner; Crystal W. Burke (Methods and Protocols)
Recommendations released by the CDC in 2023 address the need to demonstrate that the RNA genome of positive-strand RNA viruses is inactivated in addition to viral particles. This recommendation is in response to the similarities between host mRNA and the viral genome that allow the viral RNA to be used as a template by host replication mechanisms to produce infectious viruses; therefore, there is concern that through artificial introduction into host cells, active positive-strand RNA genomes can be utilized to produce infectious viruses out of a containment facility. Utilizing 10% formalin for 7 days or 2.5% glutaraldehyde/2% paraformaldehyde in 0.1 M cacodylate buffer (glut/PFA) for 2 days to fix eastern equine encephalitis virus (EEEV)-infected non-human primate (NHP) brain tissue was found to effectively inactivate EEEV particles and genomic RNA. The methods assessed in this paper outline an effective means to validate both genomic RNA and viral particle inactivation.